Impact of adding activated bentonite to thermally aged ester‐based TiO2 nanofluids on insulation performance. Issue 2 (7th March 2021) - Amalanathan, A. J.; Harid, N.; Griffiths, H.; Sarathi, R.
Abstract: The authors report the key findings from an experimental study that explored the use of activated bentonite for the reclamation of thermally aged ester‐based transformer nanofluids to improve their insulation performance. Bentonite activated with acid treatment caused an increase in the specific surface area and pore volume of bentonite compared to the bentonite sample before treatment, thus imparting an improved adsorption capability. Physico‐chemical diagnostic studies were carried out to characterise the activated bentonite. The insulation performance of the reclaimed natural ester and nano‐filled ester fluid samples was assessed by measuring the corona inception voltage and breakdown voltage of each fluid sample, apart form measuring the flow electrification current using the spinning disk method. The results revealed that the reclamation process improved the corona inception voltage, dissipation factor and the breakdown voltage of the base ester fluid sample due to attraction of carbon particles to activated bentonite, but no significant variation was observed with nanofluids due to the depletion of the electrical double layer. The flow electrification current of ester and ester nanofluids reduced after treatment with activated bentonite, may be attributed to the interaction between copper and bentonite that alters the double layer formation responsible for the separation of charges.